APPLICATION OF FLIPPED CLASSROOM AND AI BASED ON IGNASIAN PEDAGOGICAL PARADIGM IN MACHINE MODELING CLASSES - Gilang Argya Dyaksa (Universitas Negeri Semarang, 2025)
This research develops an innovative learning model in the machine modeling classroom using flipped classroom and generative AI methods and it is based on ignasian pedagogy. This research was held parallel in 2 classes, class B1 using the flipped classroom method and class B2 using conventional methods. This study aims to determine the significance of increasing final scores using the independent t-test in the application of flipped classroom in machine modeling classes with assessment rubrics based on the 4C components, namely competence, conscience, compassion, and commitment. The results of the t-test showed that the final score of class B1 was higher than class B2 even though it was not statistically significant. Although statistically insignificant, qualitative observations show that increased engagement, preparedness, and conceptual mastery among students using the FC–Gen AI–IP model. This study highlights the potential of integrating Gen AI and IP into the flipped classroom framework to enrich learning experiences in CAD-based engineering courses.